2006
DOI: 10.1111/j.1479-8298.2006.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxygen consumption in drosophilid flies from different climates

Abstract: Oxygen consumption at rest was studied in drosophilid species from cool-temperate, warm-temperate and subtropical regions to assess whether adaptations to different climates are associated with changes in metabolic rates. In experiments at 23°C using 8-day-old males of 28 species, body mass was revealed to be a significant predictor of oxygen consumption. No significant relation was detected between massadjusted oxygen consumption and latitudinal distribution or thermal tolerance by either conventional regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…5A). This is consistent with Oikawa et al (2006) showing no significant correlation between mass-adjusted oxygen consumption and thermal tolerance among 28 species belonging to Drosophila and its related genera. This may be because cold tolerance is a complex trait influenced by various factors such as presence of cryoprotective agents, antifreeze proteins, ice-nucleating proteins and heat-shock proteins and modified condition of cell membrane (Chown and Nicolson, 2004, for review;Lee and Denlinger, 2010;Michaud and Denlinger, 2010;Koštál, 2010;Chown and Sinclair, 2010;Huey, 2010;Overgaard et al, 2010;Storey and Storey, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…5A). This is consistent with Oikawa et al (2006) showing no significant correlation between mass-adjusted oxygen consumption and thermal tolerance among 28 species belonging to Drosophila and its related genera. This may be because cold tolerance is a complex trait influenced by various factors such as presence of cryoprotective agents, antifreeze proteins, ice-nucleating proteins and heat-shock proteins and modified condition of cell membrane (Chown and Nicolson, 2004, for review;Lee and Denlinger, 2010;Michaud and Denlinger, 2010;Koštál, 2010;Chown and Sinclair, 2010;Huey, 2010;Overgaard et al, 2010;Storey and Storey, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…In general, metabolic rate decreases as the ambient temperature decreases in ectothermic animals including Drosophila (Fleming and Miquel, 1983;Berrigan and Partridget, 1997;Oikawa et al, 2006), and this tendency is regarded as a response to temperature changes (e.g., Gillooly et al, 2001). However, in the studies with Drosophila and the tsetse fly species mentioned above (Berrigan, 1997;Terblanche et al, 2005;Terblanche and Chown, 2006), significant effects of the rearing temperature on the response to temperature changes were also suggested.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results are controversial because not all studies find evidence for MCA. For example, at the intraspecific level, Berrigan and Partridge (1997) found no relationship between the slope of the MR-T relationship and latitude in Drosophila melanogaster (and see Oikawa et al 2006). By contrast, at the interspecific level, Mackay (1982) found that high-altitude species of Pogonomyrmex ants have increased metabolic rates and sensitivity to temperature compared with low-elevation species.…”
Section: Temperature Relationship Is Correlated With Climate Introducmentioning
confidence: 89%
“…Alpine habitats require an organism to meet elevated ATP costs associated with growth and development at cooler temperatures (Chown and Gaston 1999; Addo-Bediako et al. 2002; Oikawa et al. 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2006). This increased demand can be met in a variety of ways, including an increase in metabolic rate (Chown and Gaston 1999; Oikawa et al. 2006), coding and transcriptional variation that influences aerobic capacity and thermal tolerance (Dalziel et al.…”
Section: Introductionmentioning
confidence: 99%